Imbalanced literacy? how a US national educational policy has affected English learners and their teachers - Sharkey, Judy (Colombian Applied Linguistics Journal, 2009)
Learning and teaching are always affected by institutional contexts and their policies, ranging from the classroom policies that teachers establish or enact—tacitly or explicitly, to the larger rings of policy set by schools, organizations, districts, states, and/or country. How is policy enacted on a local level? How does such policy affect the needs and realities of students and teachers? How does listening to teacher concerns contribute to valid critiques of policy? This article addresses those questions as they pertain to the US education policy known as No Child Left Behind (NCLB). It is told through the perspectives and experiences of six English language teachers in three public schools in one urban school district in the Northeastern United States. Although teachers’ concerns are often dismissed as anecdotal, they can offer valuable insights into the weaknesses of policies and/or programs. In the often, dichotomous worlds of policy and practice, this story highlights the critical need to attend to both.